Variation of Learning Methods to Create Effectivity of Translation Learning Procces - Asyrovi, Muchammad (Bulletin of Science Education, 2021)
Translation's learning be the one of learnings which they require specify methods. There are so many methods in Arabic learning, but not all those methods can be used in translation's learning. This article will explain about some methods that can be used in translation's learning. This research is a library research and using qualitative analysis when in analyzing the data which has a goal to spell out some variation of translation's learning methods which can use on there. The results of this study the variation of methods that can be used in translation learning are contextual teaching and learning (CTL) method, jigsawmethod, audio-lingual method, grammar-translation method, e-lerning method, and eclectic method. Keywords: Translation Method, Learning Method, Variation Learning Method